Prevalence of different types of gallstone in the patients with cholelithiasis at Kathmandu Medical College, Nepal - Pradhan, SB; Joshi, MR; Vaidya, A (Kathmandu University Medical Journal, 2010)
Background: Gallstone disease known as cholelithiasis is the most common digestive surgical disorder and account for an important part of health care expenditure. Attempt was made to analyse the gallstone for typing depending upon the composition. Aims & objectives: The main objective of this study was to see the prevalence of different types of gallstone in Nepal and to correlate them with the clinical findings. Materials & methods: Gallstones of 80 different patients who underwent cholecystectomy for cholelithiasis were collected from 20th January 2005 to 16th May 2006 in Department of Pathology, Kathmandu Medical College Teaching Hospital. Detailed history was taken. Stones were analyzed with chemical and enzymatic methods using clinical spectrophotometer. Results & conclusion: The most commonly involved age group for cholelithiasis (32.5%) is found to be 30-39 years with a female predominance (M: F=1:3.2). Cholelithiasis was found more commonly among non-vegetarian with the vegetarian: non-vegetarian ratio 1:9. Mixed type stone was found to be the most common type of stone comprising 78.75%, followed by cholesterol stone 12.5%, Brown pigment stone 7.5% and Black pigment stone 1.25%. Key words: Gallbladder; cholelithiasis; Gallstone DOI: 10.3126/kumj.v7i3.2736 Kathmandu University Medical Journal (2009) Vol.7, No.3 Issue 27, 268-271